Situation Report: Romania, 28 November 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. North Vietnamese Delegation Visits Romania in Search of Economic Aid US Secretary of Agriculture Visits Bucharest Military Delegations Exchanged with Venezuela, Guinea, and Greece Romania News Media Report on Anti-Cominform Campaign in Yugoslavia Law on Streets in Cities and Communes Changes in the Defense Council